Assessing Knowledge of Obstructive Sleep Apnoea among 4th Year and 6th Year Medical Students, Internal Medicine Registrars and Medical Consultants at the University of Cape Town - Mbena, Bulelwa Priscilla (Department of Medicine, 2023)
Introduction: Obstructive sleep apnoea (OSA) is not frequently diagnosed, despite being a common medical condition. OSA is associated with increased cardiovascular morbidity. There is no data on the prevalence of OSA in South Africa. We set out to assess knowledge of OSA among students, registrars and consultants in the department of medicine of a large South African university. Methods: This is a descriptive, cross-sectional study. We distributed an anonymous online survey among 4th and 6th year medical students, registrars and consultants in the Department of Medicine at the University of Cape Town. Results: We had a 32% response rate to our survey. The mean knowledge score was 13/18. We found a weak but significant association between age and knowledge (R=0.45, p<0.001), with a weak correlation between age and attitude (R=0.31, p<0.001), and a weak association between attitude and knowledge (R=0.3, p =0.00022). There were significant differences in level of education between undergraduates and consultants (p=0.002) as well as between undergraduates and registrars (p=0.002). Our cohort agreed that OSA is an important clinical disorder, but they lacked confidence in their ability to identify and manage patients with OSA. Conclusion: More teaching time is needed at an undergraduate level to improve the ability of clinicians to recognise and manage OSA.